Early home-supported discharge for patients with stroke in Portugal: a randomised controlled trial. (February 2017) - Santana, Silvina; Rente, José; Neves, Conceição; Redondo, Patrícia; Szczygiel, Nina; Larsen, Torben; Jepsen, Birgitte; Langhorne, Peter
Objective: To evaluate an early home-supported discharge service for stroke patients. Design: We carried out a prospective, randomised, open-label, blinded-endpoint trial (allocation ratio of 1:1) with patients assigned to either an early home-supported discharge service or usual care. Setting: The study was undertaken in Aveiro, Portugal, between April 2009 and April 2013. Subjects: We included stroke patients aged 25–85 years admitted to the stroke unit with an initial Functional Independence Measure of up to 100, who gave informed consent. Interventions: Patients in the early home-supported discharge group began their rehabilitation intervention in the stroke unit and the early home-supported discharge team worked with them at home for a maximum of one month. Patients in the control group received usual services. Main measures: The primary outcome measure was the Functional Independence Measure at six months after stroke. Results: We randomised 190 patients of whom 34 were lost to follow-up. There were no significant differences (p > 0.5) in the average scores of Functional Independence Measure between the early home-supported discharge (69 ±22; mean ±SD) and the control groups (71 ±17) measured at baseline; and between the early home-supported discharge (107 ±20) and the control groups (107 ±25) measured at six months. The number of individuals with a low Functional Independence Measure score (<60) in the early home-supported discharge group compared with the control group was higher at admission (34/95 vs. 26/95) and lower at follow-up (2/74 vs. 5/78). Conclusions: It was feasible to implement early home-supported discharge procedures in a Southern European setting, but we have not shown convincing differences in disability at six months.